Ethical Research. The Declaration of Helsinki, and the Past, Present and Future of Human Experimentation. - Frewer, Andreas; Schmidt, Ulf; Sprumont, Dominique (Oxford University Press, 2020)
At the heart of research with human beings is the moral notion that the experimental subject is altruistic, and is primarily concerned for the welfare of others. Beneath the surface, however, lies a very different ethical picture. Individuals participating in potentially life-saving research sometimes take on considerable risks to their own well-being. Efforts to safeguard human participants in clinical trials have intensified ever since the first version of the World Medical Association's Declaration of Helsinki (1964) and are now codified in many national and international laws and regulations. However, a comprehensive understanding of how this cornerstone document originated, changed, and functions today does not yet exist in the sphere of human research. Ethical Research brings together the work of leading experts from the fields of bioethics, health and medical law, the medical humanities, biomedicine, the medical sciences, philosophy, and history. Together, they focus on the centrality of the Declaration of Helsinki to the protection of human subjects involved in experimentation in an increasingly complex industry and in the government-funded global research environment. The volume's historical and contemporary perspectives on human research address a series of fundamental questions: Is our current human protection regime adequately equipped to deal with new ethical challenges resulting from advances in high-tech biomedical science? How important has the Declaration been in non-Western regions, for example in Eastern Europe, Africa, China, and South America? Why has the bureaucratization of regulation led to calls to pay greater attention to professional responsibility? Ethical Research offers insight into the way in which philosophy, politics, economics, law, science, culture, and society have shaped, and continue to shape, the ideas and practices of human research.